Sejarah Perkembangan Pendidikan Era Bani Umayyah (661-750) - Syatiri, Syahla Rana; Muhda, Muhda; Siti, Siti; Wulan, Wulan; Nurjanah, Nurjanah (Jambura History and Culture Journal, 2025)
This study aims to analyze the development of Islamic education during the Umayyad Dynasty and the factors contributing to its progress. A qualitative method with a literature review approach and documentation techniques was used to collect data from various written sources. The results indicate that Islamic education advanced significantly through a decentralized system, allowing its spread across different territories. Additionally, education encompassed not only religious teachings but also general knowledge. Various institutions, such as kuttab, mosques, literary assemblies, and palaces, played a role in education, employing lecture and demonstration methods.